FOREWORD, Pendhapa: Vol. XI, No. 1. - sumarno, sumarno (Pendhapa, 2020)
Interior design as a scientific discipline related to problem solving is in harmony with the quality of human life, living creatures, to the micro-organisms contained therein. The scope of study of Interior Design, of course, covers various aspects which are interrelated and complementary.The interrelated fields include the conditions of natural environment, social, political, cultural, traditional, and local genius of the community, which also have an influence in interior design. The combination between/of these interrelated aspects can produce unique and distinctive interior design works.Being consistent with the previous editions, volume XI, number 1, Pendhapa: Journal of Interior Design, Art and Culture this edition presents nature-social environment as an idea in the interior design of a music school, written by W Ranta Cosynala and Ahmad Fajar Ariyanto, entitled â€œThe Interior Design of a Music School for Persons with Vision Impairment With the Concept of Landmark Perception in Surakarta, Indonesiaâ€.Two articles in this edition highlight interior design with the integration between natural environments and culture. The natural wealth and biological features of plants that inspire the designers for the making of batik motifs become the themes that, then, are actualized in the design. Anam Nur Cahyono and Indarto captured the potential of the surrounding nature with its natural beauty and cool weather in the design of Candi Loka Restaurant Ngawi, East Java, Indonesia. The unification of interior design with its natural and cultural atmosphere is reflected on the highlighted theme that is batik with tea leaves motif. The shape, color, and character of the tea leaves are explored as elements of unifying designs. The article entitled Interior Designing of Semarang Convention Center under the Theme of Asem Arang-Arang, by Devi Wijiyanto and Sumarno also highlighted thewealth and the uniqueness of local culture associated with natural wealth as its identity. Asem as an icon of the city of Semarang, Central Java, Indonesia is then used as a design idea and design theme.The design based on the natural wealth of culture is unavoidable because it concerns the universality of human-beings in which they grow and develop. Identity is a gift that exists in every human being, as a universal thing. The relationship between culture and universal human nature is very close that the design should also consider its universality aspect.Rangga Firmansyah and his friends researched the importance of a system for interior design to help people with special needs. Interior designs should accommodate the universal characteristics of people with disabilities or special needs to have the same opportunity to access user-friendly and barrier-free facilities. Some limitations are also felt by nursing mothers in breastfeeding their children, especially when they are in public spaces. Siti Badriyah and I Nyoman Suyasa write a research article on the convenience and ergonomics aspects of lactation rooms in public spaces, especially in the several public general hospitals in Surakarta, Central Java, Indonesia.Â Chief EditorSumarno.